Addressing Multicultural Issues in Communication Sciences and Disorders. - Horton-Ikard R; Muñoz ML (Contemporary Issues in Communication Science & Disorders)
Purpose: The purpose of this study was to examine current practices for promoting multicultural competence in communication sciences and disorders (CSD) training programs using the Multicultural Competency Checklist (MCC; Ponterotto, Alexander, & Grieger, 1995). The MCC consists of 22 statements and was designed to guide multicultural program development in counseling psychology in six competency areas: (a) minority representation, (b) curriculum issues, (c) counseling practice and supervision, (d) research considerations, (e) student and faculty competency evaluation, and (f) physical environment. Method: The MCC was mailed to 227 CSD training programs that had been accredited by the American Speech-Language-Hearing Association. Completed surveys were received from personnel at 133 programs. Results: Attainment of a particular competency ranged from 14% to 96%. The vast majority of CSD training programs met competencies in the area of curriculum issues. However, few programs met competencies related to minority representation. Conclusion: CSD training programs report numerous efforts to address the need for multicultural training. However, additional efforts are necessary to ensure continued development of a conceptually driven academic infrastructure that supports multicultural education in CSD.